Penerapan Sistem Informasi Dalam Membantu Kegiatan Stok Opname Barang Store Paris Baguette Puri Mall - Teti Desyani; Refli Wijaya; Mohamad Yudha Mauluda; Muhammad Rizal Abdul Aziz (Jurnal Riset Informatika dan Inovasi, 2024)
This report discusses the implementation of an information system to assist stock opname of goods at Store Paris Baguette Puri Mall. Currently, the stock opname process is still carried out manually by writing it down in a large book that is stored on the kitchen shelf. This causes several inefficiencies, such as: Slow and time-consuming process: Recording stock opname manually takes a long time and is prone to errors, unsafe data: Stock opname ledgers are stored on kitchen shelves that are not secure and easily lost or damaged, data is difficult to find: Searching for stock opname data in ledgers takes a lot of time and effort. Therefore, this study aims to implement a web-based or mobile application information system to assist the stock opname process at Store Paris Baguette Puri Mall. This system is expected to:Increase the efficiency of the stock opname process: This system can help speed up the stock opname process and minimize errors, improve data security: Stock opname data is stored securely in a database and can be easily accessed, make data retrieval easier: Stock opname data can be easily and quickly searched through the system. It is hoped that with the implementation of this information system, the performance of Store Paris Baguette Puri Mall will be better and can save time and costs.